Analisis Video Pembelajaran Materi Teks Berita pada Kanal Youtube untuk Pembelajaran Bahasa Indonesia - Andini, Salsabilla; Setyonegoro, Agus; Priyanto, Priyanto (Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study aims to find out what are the learning videos of news text material that are already on YouTube based on the characteristics, specifications, and the advantages and disadvantages of the videos. This study uses a type of qualitative descriptive research. The data analysis technique uses the data analysis technique Miles and Huberman. This research gets results with videos that are generally 5-10 minutes long, in general the videos are in accordance with KD, indicators and learning objectives of news texts. Apart from that, video specifications are obtained with an aspect ratio of 16:9, resolution of 720 (HD), and a frame rate of 30fps. There are 40 learning videos on YouTube analyzed based on Miles and Huberman according to research criteria and a review of learning videos, 22 learning videos for news texts are found to be appropriate. Video material regarding identification of news elements and identification of news elements and concluding news content.